FROM TASTE TO TEXT: A CORPUS-BASED ANALYSIS OF FIGURATIVE LANGUAGE PATTERNS AND RHETORICAL QUALITY IN NOVICE EFL CULINARY DESCRIPTIONS - Putri, Rahmadila Eka; Nasution, Mutia; Prananda, Pramudia; Rasya, Muhammad (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This study investigated the patterns and rhetorical quality of figurative language in novice EFL writers’ descriptive texts about real culinary objects using quantitative corpus-based design supported by qualitative rhetorical evaluation. To generate the dataset, 42 first-semester learners in Narrative & Descriptive Writing course produced forty-two 500-word descriptions, forming a small corpus. The texts were manually coded using an instrument covering five figurative categories namely simile, metaphor, personification, hyperbole, and onomatopoeia. Two raters identified and classified all items to ensure reliability, guided by an analytic rubric assessing Contextual Appropriateness, Stylistic Effectiveness, and Creativity Response. The corpus contained 680 expressions, comprising 265 similes, 143 metaphors, 116 personifications, 101 hyperboles, and 55 instances of onomatopoeia. Simile dominated but demonstrated reliance on explicit comparative markers, whereas metaphor exhibited limited conceptual mapping. Personification contributed the strongest stylistic value, while hyperbole often led to overstatement and onomatopoeia appeared sparsely as isolated sound cues. Despite high figurative density, overall rhetorical effectiveness remained moderate, with creativity identified as the weakest dimension. The findings indicate that learners’ figurative use is active yet formulaic. Pedagogically, the study highlights the need for explicit instruction, corpus-informed modelling, and guided revision to support more intentional and stylistically effective descriptive writing.